Knowledge, attitudes and management skills of medical practitioners regarding weight management - Vangile B. Mkhatshwa; Gboyega A. Ogunbanjo; Langalibalele H. Mabuza (AOSIS, 2016)
Background: Overweight and obesity have become a global problem. Health professionals are poorly prepared in weight management, which has an effect on their attitudes and management skills with regard to overweight and obese patients. Aim and setting: To assess the knowledge, attitudes and management skills of medical practitioners regarding weight management at Odi District Hospital, Gauteng Province, South Africa. Methods: We conducted a cross-sectional study on 48 medical practitioners at Odi Hospital between 01 October and 31 October 2013. A self-administered questionnaire was used to assess their knowledge, attitudes and management skills in weight management. The SPSS® statistical software (Version 22) was used for data analysis. A p < 0.05 was considered significant. Results: Fifty medical practitioners were recruited, 48 consented to participate and 28 (58.3%) were male. Their categories were community service doctors (3), medical officers (21), registrars (22) and others (2). Thirty-seven (77.1%) never received training in weight management (p < 0.001). Thirty-two (66.7%) regarded weight management as not confined to a dietician (p < 0.001) and 27 (56.2%) regarded weight management as usually unsuccessful (p = 0.004). Forty-seven (97.9%) provided lifestyle modifications and 43 (89.6%) involved the patient's family in weight management (p < 0.001). More non-registrars [14 (77.8%)] than registrars [8 (38.1%)] measured the body mass index (BMI) routinely (p = 0.013). Conclusion: Few medical practitioners received training in weight management. They regarded weight management as usually unsuccessful and lacked confidence in the same owing to lack of training. They provided lifestyle modifications and involved the patient's family in weight management. Non-registrars measured the BMI routinely. There is a need for training in weight management at undergraduate and post-graduate levels.